Genetic factors underlying attention and impulsivity: mouse models of attention-deficit/hyperactivity disorder. (April 2015) - Itohara, Shigeyoshi; Kobayashi, Yuki; Nakashiba, Toshiaki
Highlights: ADHD mouse models have diversified due to the progress in human genetics. Causal genes act on monoaminergic signaling, synaptic plasticity, and development. Gene–gene interactions have crucial roles in attention and impulsivity. Gene–environment interactions have crucial roles in attention and impulsivity. Mouse models have several advantages for future studies. Abstract : Increasing evidence suggests complex genetic factors for attention-deficit/hyperactivity disorder (ADHD). Animal models with definitive genetic characteristics are indispensable for gaining an understanding of the molecular, cellular, and neural circuit mechanisms underlying ADHD. Toward this aim, mice have several advantages because of their well-controlled genetic backgrounds and the relative ease with which functions of defined neuronal circuits can be manipulated. Dopamine signaling dysfunction was once the major pathogenic focus of interest in ADHD research, but hypotheses have expanded to include functionally distinct molecules. Forward and reverse genetic approaches have produced diverse mouse genetic models for genes involved in monoaminergic signaling, synaptic plasticity, and neuronal circuit formation. Data suggest crucial roles of gene–gene interactions and gene–environment interactions in the pathophysiology of ADHD.